Pengaruh Corporate Social Responsibility Terhadap Profitabilitas dan Dampaknya Terhadap Nilai Perusahaan Sektor Pertambangan di Bursa Efek Indonesia Tahun 2016-2018 - Primasa Minerva Nagari; Tatas Ridho Nugroho; Hari Setiono (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2019)
Corporate Social Responsibility is an activity carried out by a company as the responsibility of its operational activities. This is also done as an effort to increase profitability and company value. This study aims to determine the effect of Corporate Social Responsibility on firm value with profitability as an intervening variable. This research was conducted by simple regression analysis and path analysis. The result is that Corporate Social Responsibility has no effect on firm value through profitability as an intervening variable because the direct influence of Corporate Social Responsibility on company value is 0.255 greater than the standardized coefficient beta value of the indirect effect of CSR on firm value through profitability of 0.0180.